Estrogen/androgen balance in men with hyperestrogenism normalized by using letrozole of the aromatase inhibitor drug class - Z. Sh. Pavlova (Акушерство, гинекология и репродукция, 2022)
Introduction. Currently, virtually no data on comparative studies of efficacy and safety of drug class aromatase inhibitors vs. standard therapies used in patients with overweight and/or obesity with an initial testosterone deficiency and excessive estradiol are available.Aim: to study and evaluate the efficacy and safety of the use of the reversible aromatase inhibitor letrozole in adult men with overdeveloped adipose tissue and/or obesity with hyperestrogenism and testosterone deficiency.Materials and Methods. A randomized, open, interventional, comparative, single-centre clinical trial was conducted by enrolling 49 obese men. The patients were divided into 2 groups: Group 1 (n = 26) – patients received standard metformin therapy (1000 mg 2 times a day), along with letrozole (at a dose of 2.5 mg 2 times a week); Group 2 (n = 23) – patients received only standard metformin therapy. Patients were monitored for 8 weeks from the date of inclusion. Anthropometric parameters were monitored: body weight, body mass index, waist as well as hip circumference. Laboratory data were also evaluated: level of sex hormone binding globulin (SHBG), total testosterone, estradiol, glucose, uric acid, insulin. All subjects filled out questionnaires twice (before the start of the study and after its completion) – the aging symptoms questionnaire for men (Aging Males Symptoms, AMS) and IIEF (International Index of Erectile Function).Results. Total testosterone level significantly and reliably increased only in Group 1 from 10.6 to 22.2 nmol/L. In Group 2 testosterone level increased insignificantly from 9.28 to 11.02 nmol/L, and did not reach the physiological normal range. Estradiol changes also differed markedly and significantly: in Group 1, estradiol decreased from 51.4 to 24.3 pg/ml, i.e., by 2.1-fold reaching physiological range, whereas in Group 2 estradiol level decreased insignificantly from 45.1 to 44.4 pg/ml, and remained above the range of normal values. Significant changes in SHBG were observed only in Group 2. Insulin level in Group 1 significantly decreased from 10.6 to 6.6 μIU/ml, i.e., by 1.6-fold. In Group 2, insulin also decreased, but less pronounced, from 15.8 to 13.7, i.e., by 1.2-fold, which turned out to be statistically insignificant and according to the НОМА-IR index (Homeostasis Model Assessment of Insulin Resistance), it remained within the insulin resistance range. Glucose level did not change significantly in both groups. Uric acid, on the contrary, significantly changed in both groups: in Group 1, from 0.41 to 0.35 mmol/L, and in Group 2, from 0.40 to 0.36 mmol/L.Conclusion. The use of letrozole significantly increases total testosterone level in patients with initial testosterone deficiency and hyperestrogenism. At the same time, patients with androgen deficiency and hyperestrogenism, in most cases, have excess body weight due to adipose tissue, metabolic syndrome in a combination of its various components, which underlie a need to use standard methods of therapy primarily modified lifestyle and metformin, which provide the maximum positive effect in the treatment of such patients.